Antibody-dependent and phytohaemagglutinin-induced lymphocyte cytotoxicity in systemic lupus erythematosus. Issue 1 (February 1981) - Wright, J K; Hughes, P; Gelsthorpe, K; Ward, A M; Rowell, N R
Abstract : An investigation of cell-mediated cytotoxicity in 22 patients with systemic lupus erythematosus (SLE), using both whole blood and purified peripheral blood mononuclear cells (PBM) to measure antibody-dependent (ADCC) and phytohaemagglutinin (PHA)-induced lymphocyte cytotoxicity for Chang liver cells, has revealed 2 distinct abnormalities in patients with active disease. PHA-induced cytotoxicity was found to be selectively reduced in whole blood assays only (P less than 0.05), whereas ADCC was impaired in both whole blood (P = 0.02) and PBM (P less than 0.05) assays, when comparison was made with 52 normal controls. The addition of patients' sera to corresponding assays utilizing control PBM confirmed that the impaired PHA-induced cytotoxicity resulted from circulating inhibitory serum factors. Surprisingly little effect, however, was exerted on ADCC assays. These findings suggest that there is a reduction in numbers and/or functional capacity of Fc-receptor cells in active SLE, which may have pathogenetic implications.